2013
DOI: 10.1111/dme.12254
|View full text |Cite
|
Sign up to set email alerts
|

Importance of factors determining the low health‐related quality of life in people presenting with a diabetic foot ulcer: the Eurodiale study

Abstract: The factors that determine health-related quality of life are diverse and to an extent not disease-specific. To improve health-related quality of life, treatment should not only be focused on ulcer healing but a multifactorial approach by a specialized multidisciplinary team is also important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 24 publications
7
71
0
4
Order By: Relevance
“…In unadjusted analyses, we found decreased healing for several EQ-5D domains. As reported elsewhere, all domains of HRQoL at baseline were affected by both patient characteristics, such as inability to stand or walk without help, and by ulcer-related factors, such as ulcer size or limb-threatening ischemia (3,4). These factors are also associated with ulcer healing, which may further explain why we did not observe an independent effect of HRQoL on healing after correction for these factors.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In unadjusted analyses, we found decreased healing for several EQ-5D domains. As reported elsewhere, all domains of HRQoL at baseline were affected by both patient characteristics, such as inability to stand or walk without help, and by ulcer-related factors, such as ulcer size or limb-threatening ischemia (3,4). These factors are also associated with ulcer healing, which may further explain why we did not observe an independent effect of HRQoL on healing after correction for these factors.…”
Section: Discussionsupporting
confidence: 59%
“…Already at the initial presentation in the foot clinic, DFU patients report severely hampered health-related quality of life (HRQoL) (4). Several studies have clearly shown that self-assessed health status is an independent predictor of mortality in a general population, beyond the numerous other risk factors known to be associated with increased mortality (5).…”
mentioning
confidence: 99%
“…41, 47 Hopman et al 41 described that male patients with younger age, pain, problems with their mobility, or daily activities, as well as anxiety at their first visit, benefit the most from possible interventions regarding especially their mentally orientated QoL. Vice versa Hopman et al 41 concluded that vulnerable subgroups are those with pain, anxiety and depression at first visit.…”
Section: Depression and Limited Mobilitymentioning
confidence: 99%
“…This complication almost affects 50% of patients and accounts for nearly 80% of all nontraumatic amputations of the lower limb [3,4]. The disease represents nearly 35% of all hospital admissions in diabetic specialized clinics [3].…”
Section: Introductionmentioning
confidence: 99%